A Pilot Study of Low-Dose Craniospinal Irradiation in Patients With Newly Diagnosed Average-Risk Medulloblastoma - Minturn, Jane E.; Mochizuki, Aaron Y.; Partap, Sonia; Belasco, Jean B.; Lange, Beverly J.; Li, Yimei; Phillips, Peter C.; Gibbs, Iris C.; Fisher, Paul G.; Fisher, Michael J.; Janss, Anna J. (Frontiers in Oncology, 2021)
Purpose: Medulloblastoma is one of the most common malignant brain tumors in children. To date, the treatment of average-risk (non-metastatic, completely resected) medulloblastoma includes craniospinal radiation therapy and adjuvant chemotherapy. Modern treatment modalities and now risk stratification of subgroups have extended the survival of these patients, exposing the long-term morbidities associated with radiation therapy. Prior to advances in molecular subgrouping, we sought to reduce the late effects of radiation in patients with average-risk medulloblastoma. Methods: We performed a single-arm, multi-institution study, reducing the dose of craniospinal irradiation by 25% to 18 Gray (Gy) with the goal of maintaining the therapeutic efficacy as described in CCG 9892 with maintenance chemotherapy. Results: Twenty-eight (28) patients aged 3-30 years were enrolled across three institutions between April 2001 and December 2010. Median age at enrollment was 9 years with a median follow-up time of 11.7 years. The 3-year relapse-free (RFS) and overall survival (OS) were 79% (95% CI 58% to 90%) and 93% (95% CI 74% to 98%), respectively. The 5-year RFS and OS were 71% (95% CI 50% to 85%) and 86% (95% CI 66% to 94%), respectively. Toxicities were similar to those seen in other studies; there were no grade 5 toxicities. Conclusions: Given the known neurocognitive adverse effects associated with cranial radiation therapy, studies to evaluate the feasibility of dose reduction are needed. In this study, we demonstrate that select patients with average-risk medulloblastoma may benefit from a reduced craniospinal radiation dose of 18 Gy without impacting relapse-free or overall survival. ClinicalTrials.gov identifier: NCT00031590